EXPLORING NOMINALIZATION USE IN GRADUATE THESIS ABSTRACTS: AN SFL APPROACH TO ACADEMIC WRITING - Ilzam Mahfudurido; Albert Tallapessy; Dina Dyah Kusumayanti (UIN Raden Mas Said Surakarta, 2021)
Abstract becomes the mandatory part of an article which should be concise and lexically condensed. Unfortunately, not all academic writers can meet this demand. Following Halliday & Matthiessen’s (1999) types of the grammatical metaphor in which the nominalization plays as the main tendency of the construal, this study investigates nominalization cases and how they are manifested in the texts. Seven graduate students’ thesis abstracts of the Linguistics Department of a state university in Indonesia were opted as the object of the investigation. Each instance of the nominalization was coded, counted, and classified to decide their types and an in-depth elaboration of how they are manifested in the texts is provided as well. The results showed that the graduate students employed all types of the nominalization to increase the abstracts’ conciseness. The Process nominalization realized from the process-thing transference highly dominates the abstracts. The findings also reveal a wide gap of the nominalization use between the process nominalization and the other types indicating the students’ lower intermediacy of the nominalization mastery in the academic writing. Therefore, the explicit teaching of the nominalization is highly recommended as this could be of value to the students involved in the scientific publication in this university.